LncRNA PCAT1 activates SOX2 and suppresses radioimmune responses via regulating cGAS/STING signalling in non‐small cell lung cancer. Issue 4 (12th April 2022) - Gao, Yanping; Zhang, Nannan; Zeng, Zihang; Wu, Qiuji; Jiang, Xueping; Li, Shuying; Sun, Wenjie; Zhang, Jianguo; Li, Yangyi; Li, Jiali; He, Fajian; Huang, Zhengrong; et al.
Abstract: Background: The expression of long non‐coding RNA (lncRNA) prostate cancer‐associated ncRNA transcripts 1 (PCAT1) is increased in non‐small cell lung cancer (NSCLC). It stimulates tumour growth and metastasis, but its role in the radioimmune responses remain unknown. We aimed to explore the impacts of PCAT1 on tumorigenesis and radioimmune responses and the underlying molecular mechanisms in NSCLC. Methods: Comprehensive bioinformatics analysis was performed to identify immunosuppressive lncRNAs involved with tumour invasion in NSCLC. The expression levels of PCAT1 were analysed by in situ hybridisation in 55 paired NSCLC tissues and adjacent normal tissues. Both loss‐ and gain‐of‐function assays were performed to examine the effects of PCAT1 and SOX2 on NSCLC cell behaviours in vivo and in vitro. Bioinformatic analyses, chromatin isolation by RNA purification (ChIRP) and dual‐luciferase reporter assays were applied to validate the regulatory effects of PCAT1 on SOX2 expression. Chromatin immunoprecipitation, luciferase and rescue assays were utilised to identify the relationship between SOX2 and the cGAS/stimulator of interferon genes (STING) signalling. Results: PCAT1 was immunosuppressive and related with NSCLC invasion. Increased PCAT1 was negatively correlated with immune cell infiltration in NSCLC. PCAT1 knockdown restrained proliferation, increased apoptosis, and repressed cell metastasis in vivo and in vitro. PCAT1 activated SOX2 that accelerated tumorigenesis and immunosuppression. SOX2 promoted tumour growth through inhibiting cytotoxic T‐cell immunity. Moreover, SOX2 restrained cGAS transcription and hampered downstream type I interferon (IFN)‐induced immune responses. Inhibition of PCAT1/SOX2 in collaboration with radiation further inhibited tumour growth, and initiated the cGAS/STING signalling pathway, which enhanced the immune responses of radiotherapy in NSCLC. Conclusions: PCAT1/SOX2 axis promoted tumorigenesis and immunosuppression through inhibition of cGAS/STING signalling‐mediated T‐cell activation. Inhibition of PCAT1 and SOX2 synergised with radiotherapy to activate the immune response and could serve as potential therapeutic targets. Abstract : LncRNA PCAT1 is highly expressed immunosuppressive in NSCLC via downregulating cGAS/STING signalling pathway. LncRNA PCAT1 upregulates SOX2 transcription and SOX2 downregulates cGAS transcription. LncRNA PCAT1 suppresses radioimmune responses through SOX2/cGAS/STING pathway and its downregulation increases the inhibitory effects of radiotherapy in NSCLC.